Innovations in e-business - new ways of delivery of food products over the Internet in the opinion of potential customers = Innowacje w e-biznesie - nowe sposoby dostarczania produktów spożywczych zakupionych poprzez Internet w opinii potencjalnych klientów - Moroz, Mirosław (Zielona Góra: Faculty of Economics and Management Press)
According to research online sales of food enjoy bigger and bigger Internet users interest. However, selling online such products isn't free from logistic costs connected with the necessity of the geographically-spread client on the one hand and an indispensably fast delivery of food on the other hand. This article aims at presenting an innovative Freshbox project that may solve the last mile issue in online grocery.
Keywords: innowacje; e-biznes; problem ostatniej mili; innovation; e-business; last mile problem